2007
DOI: 10.1093/ndt/gfl666
|View full text |Cite
|
Sign up to set email alerts
|

The association of higher depressive symptoms and sexual dysfunction in male haemodialysis patients

Abstract: The presence of depressive symptoms, highly prevalent in haemodialysis patients, is an independent factor of sexual dysfunction in male haemodialysis patients. In a comprehensive approach to the management of sexual dysfunction, a thorough evaluation of psychological depression must be included.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
2
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 21 publications
3
58
2
3
Order By: Relevance
“…Studies examining the factors affecting the quality of life have started to increase in recent years, and particularly, SD and anxiety and depression symptoms are suggested to be important variables affecting the quality of life (2,14,15,16,17,18,19,20). Peng et al (21) reported that advanced age, diabetes, and depressive symptoms are independently related to SD and that the quality of life of patients with SD is lower. Although the studies frequently report evidences suggesting that SD affects the quality of life, there are also contradicting reports (22).…”
Section: Introductionmentioning
confidence: 99%
“…Studies examining the factors affecting the quality of life have started to increase in recent years, and particularly, SD and anxiety and depression symptoms are suggested to be important variables affecting the quality of life (2,14,15,16,17,18,19,20). Peng et al (21) reported that advanced age, diabetes, and depressive symptoms are independently related to SD and that the quality of life of patients with SD is lower. Although the studies frequently report evidences suggesting that SD affects the quality of life, there are also contradicting reports (22).…”
Section: Introductionmentioning
confidence: 99%
“…Because subjects who were visited at their place of residence did not answer the depression scale, we examined the effect of the consequent selection bias by comparing age difference between subjects included in the analysis and those excluded. Based on the IIEF-5 score of 18, the subjects were divided into the ED group (0-17) and the normal group (18)(19)(20)(21)(22)(23)(24)(25) 3 In addition, the odds ratio of ED according to depression level was obtained through logistic regression analysis. We calculated both the age-adjusted odds ratio, which adjusted only age, and the multivariate-adjusted odds ratio, which adjusted all ED-related factors.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study are consistent with the results of many previous cross-sectional studies. 2,9,12,[20][21][22][23][24] In the MMAS, a cross-sectional study (N ¼ 1265) conducted from 1986 to 1989 with randomly sampled men aged between 40 and 70 years who were aging normally and healthily, the odds ratio of moderate or completed ED with adjusting related factors was 1.8 (95% CI ¼ 1.21-2.73) in depressive subjects (16XCED-S (the Center for Epidemiological Study's Depression scale)) compared with non-depressive ones. 9 The authors formulated a model for understanding the complex and dynamic relation between depression and ED, which is based on the disablement process applying by Verbrugge and Jette.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have observed strong associations between erectile dysfunction, depression, and adverse cardiovascular outcomes (8,(17)(18)(19)50), although a causal link has not been definitively established (18). Of the trials included in our meta-analysis, none considered these patientlevel outcome parameters.…”
Section: Comparison With Other Studiesmentioning
confidence: 97%